Automated sample preparation for mercury analysis in wood materials. Issue 5 (1st August 2016) - Vorberg, Ellen; Fleischer, Heidi; Junginger, Steffen; Stoll, Norbert; Thurow, Kerstin
Abstract : Laboratories that provide element‐specific measurements will gain on improved quality and better economical results by automating the required sample pre‐treatment. Commercially available, automated workstations are usually configured for handling the standardised multi‐titer‐plate‐format facilitating biological applications. In contrast, automating analytical processes, such as element‐specific applications, is still an unsolved challenge due to the required, specific process conditions. Therefore, the purpose of the presented work was the design and the realisation of an automated system providing precise sample pre‐treatment for element‐specific measurements. Finally, the developed system was successfully evaluated and ensures reliable sample pre‐treatment. The designed, flexible performance solution enables both system adaption and simultaneous sample handling. Moreover, the developed system allows for environmental investigations in a 24/7 manner. The results of the automated mercury analysis are in excellent agreement with the true value corresponding to a level of confidence of ∼95% ( P = 95%) while using referenced and real wood materials.